The response of red duikers Cephalophus natalensis to drive counts - A.E. Rowland (Koedoe: African Protected Area Conservation and Science, 1990)
The response of red duikers to drive counts conducted on three consecutive days was monitored. The disturbance level to the duiker community of this counting method is low, an it is unlikely to have any long-term effects. The red duiker flees rather than hides from the counting line, thereby increasing its chances of being counted.